The Taylor rule and interest rate uncertainty in the US 1970-2006 - Martin Mandler (Philipps-University Marburg, Faculty of Business Administration and Economics, 2009)
This paper shows how to estimate forecast uncertainty about future short-term interest rates by combining a time-varying Taylor rule with an unobserved components model of economic fundamentals. Using this model I separate interest rate uncertainty into economically meaningful components that represent uncertainty about future economic conditions and uncertainty about future monetary policy. Results from estimating the model on U.S. data suggest important changes in uncertainty about future short-term interest rates over time and highlight the relative importance of the different elements which underlie interest rate uncertainty for the U.S.
Keywords: E52; C32; C53; 330; Monetary policy; reaction functions; state-space models; output-gap forecasts; inflation forecasts